Investment Decisions through Total Asset Growth toward Price to Book Value on the Jakarta Islamic Index - Syaugi Syaugi; Aulia Rahmah (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This research analyzes the eﬀect of investment decisions through Total Asset Growth (TAG) on Price to Book Value (PBV). Since PVB indicates stock measurement based on the ratio of stock price to book value, it is used by investors to assess the price oﬀered. This research uses time-series data from 2014-2020 to examine seven companies selected using purposive sampling but based on fairly good asset developments from 2014 to 2020. Furthermore, this quantitative causal study data were collected using documentation from various sources and analyzed using a simple linear regression test. The results show that the TAG variable has no eﬀect on PBV with a signiﬁcance value of 0.89 0.05. This shows that TAG does not describe a stable company and is not always useful in investment decision-making.